(untitled) (Revista Iberoamericana de Bioética, 2023)
In Peru, the decentralization of mental health services and the prioritization of resources in primary care represent key actions for mental health development in the country. However, the persistent sociocultural and economic barriers in the population hinder access to mental health services, a situation that has worsened during the COVID-19 pandemic. This research aims to analyze caregiver experiences in primary mental health care at a counselling center in Metropolitan Lima between 2020 and 2021. Through narrative analysis, the results show that the pandemic has exacerbated psychological, social and material vulnerabilities in both caregivers and users. This unveils the need to provide constant training and group supervision processes to guarantee self-care and group-care for mental health practitioners, as well as the quality of the service provided.